1995
DOI: 10.1111/j.1476-5381.1995.tb15887.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin receptors in mouse and rat isolated superior cervical ganglia

Abstract: 1 The ability of bradykinin and its analogues to depolarize rat and mouse superior cervical ganglia was studied by use of in vitro grease-gap recording techniques, and the ability of antagonists selective for bradykinin receptor subtypes to block their effects was examined.2 Bradykinin (3pM) depolarized ganglia from both species, although the magnitude of the maximal response was less in mouse (15 + 5%, n = 7) than rat tissue (33 ± 6%, n = 7), relative to muscarine(1 M).3 Interleukin lfP (30 u mlP' for 18 h at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…CGRP release causes a powerful dilation of arterioles and thus facilitates plasma extravasation by increasing local blood flow (Brain and Williams 1985). The activation of sympathetic neurons occurs through B 2 receptors coupled with the second messenger protein kinase C and involves the inhibition of an M-type potassium current (Babbedge et al 1995;Jones et al 1995;Chulak et al 1995;Seabrook et al 1995). In keeping with this, sympathetic neurons have been shown to be involved in bradykinin-mediated mechanical hyperalgesia via release of prostanoids and possibly other sympathomimetics (Taiwo and Levine 1988;Khasar et al 1995).…”
Section: Other Sensitization Mechanismsmentioning
confidence: 92%
“…CGRP release causes a powerful dilation of arterioles and thus facilitates plasma extravasation by increasing local blood flow (Brain and Williams 1985). The activation of sympathetic neurons occurs through B 2 receptors coupled with the second messenger protein kinase C and involves the inhibition of an M-type potassium current (Babbedge et al 1995;Jones et al 1995;Chulak et al 1995;Seabrook et al 1995). In keeping with this, sympathetic neurons have been shown to be involved in bradykinin-mediated mechanical hyperalgesia via release of prostanoids and possibly other sympathomimetics (Taiwo and Levine 1988;Khasar et al 1995).…”
Section: Other Sensitization Mechanismsmentioning
confidence: 92%
“…Some painful processes are mediated by sympathetic activity ( Woolf & Mannion, 1999 ). Interestingly, functional B 1 receptors are expressed in sympathetic ganglia, since their activation is able to depolarize superior cervical ganglia neurones in vitro ( Seabrook et al ., 1995 ; 1997 ). Postganglionic sympathetic terminals have been demonstrated to be involved in B 1 receptor agonist‐induced hyperalgesia ( Khasar et al ., 1995 ).…”
Section: Participation Of Kinin B1 Receptors In Painful Processesmentioning
confidence: 99%
“…Regulation of B1 bradykinin receptor expression has been studied mostly in isolated smooth muscle preparations and primary cultures of smooth muscle cells, where it has been demonstrated that cytokines, including IL-Ip, can upregulate receptor expression (e.g. DeBlois et at., 1991; Bathon et at., 1992; Levesque et at., 1993;Galizzi et al, 1994;Seabrook et al, study pretreatment of primary cultures IL-I/i, (using incubation times ranging failed to induce specific [3H]-des-Arg'0-kallidin although specific B1 bradykinin receptor WI38 which express B1 bradykinin receptors upregulated by the same concentration IL-Ifl incubation times. In cultured cells, induction be observed from 2 h up to 24 h after IL-1Ip (Levesque et al, 1993;Galizzi et al, 1994) with IL-Ifl can induce B1 bradykinin receptor-mediated hyperalgesia that is maintained for up 1994).…”
Section: Experiments In Cultured Drg Neuronesmentioning
confidence: 99%
“…Possible mechanisms of B. bradykinin receptor-mediated hyperalgesia As B1 bradykinin receptors do not appear to be expressed on sensory neurones, it is possible that the receptors involved in inflammatory hyperalgesia are located on sympathetic neurones. Bradykinin receptors have been shown to have hyperalgesic effects via the sympathetic nervous system (Levine et al, 1986;Lee et al, 1991) and a recent study in the superior cervical ganglion showed that, although the predominant form of bradykinin receptor was the B2 bradykinin receptor subtype, there was evidence for B1 bradykinin receptor-mediated depolarization after treatment with a combination of IL-hi and captopril (Seabrook et al, 1995). This is in contrast, however, to a study by Babbedge et al (1995), also in the superior cervical ganglion, who were unable to demonstrate any evidence for B1 bradykinin receptor-mediated depolarization even after prior administration of bacterial lipopolysaccharide.…”
Section: Experiments In the Spinal Cord And Tail Preparationmentioning
confidence: 99%